2019
DOI: 10.1109/access.2019.2949465
|View full text |Cite
|
Sign up to set email alerts
|

Social Network-Oriented Learning Agent for Improving Group Intelligence Coordination

Abstract: Group coordination is embedded in social networks, which aims to reach a consensus or solve conflicts among social individuals. Recently, improving performance has become a challenging task and drawn considerable interest in this field. To eliminate barriers of group coordination, we abstract the problem into a networked color coordination game and introduce learning agents encoded with Q-learning to collect local information and learn local individual behaviors. We first show that learning agents can effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…We incorporate random behavior in various decision stages in the following modified update rules based on the basic greedy update rule above. Notably, these simple yet natural update rules based on intuitive heuristics, combined with the bipartite network structure which simplifies the possible colorings, enable analytical insights that are unobtainable in the more complicated systems put forward in other work ( Qi et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We incorporate random behavior in various decision stages in the following modified update rules based on the basic greedy update rule above. Notably, these simple yet natural update rules based on intuitive heuristics, combined with the bipartite network structure which simplifies the possible colorings, enable analytical insights that are unobtainable in the more complicated systems put forward in other work ( Qi et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, they also found that the bots could be detrimental if not properly tuned with the appropriate levels of randomness ( Shirado and Christakis 2017 ). Along this line, a recent related modeling work has incorporated reinforcement learning algorithms (q-bots) into agent-based simulations of the distributed coloring problem ( Qi et al., 2019 ). Despite these developments, there still is a lack of analytical insights into the optimal level of random behavior needed when solving network coloring problems.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the impact of bots with small noise was comparable to assigning nodes with fixed colors, directly corresponding to committed individuals, to achieve compatibility with a global solution. Other related numerical or theoretical solutions to this problem include reinforcement learning algorithms (q-bots) or myopic artificial agents [33,34]. Although these studies employed more sophisticated algorithms than simply designing agents with colors, the notion of committed individuals persists, as these preprogrammed bots maintained consistent strategies without adaptation.…”
Section: Color Coordination Gamementioning
confidence: 99%
“…Related topics include shoals of fish [2]- [8], flocks of birds [9], [10], swarms of locusts [11]- [13], communities of bacteria [14], [15], groups of microtubules [16], masses of histiocytes [17], [18], streams of traffic and flows of humans [19], [20]. A relatively simple and local interaction between individuals produces coordinated and ordered collective behaviors such as these [21]. In this way, biological groups show various intelligent characteristics (distribution, self-adaption, and robustness) that cannot be achieved by a single individual in all kinds of situations.…”
Section: Introductionmentioning
confidence: 99%